Influence of various sintering parameters and the temperature dependent scaling on the dynamic hysteresis behavior of Ba0.9Ca0.05Sr0.05T0.85Zr0.15O3 ceramics. Issue 1 (27th June 2020) - Suresh, P.; Mathiyalagan, P.; Srikanth, K.S.
Abstract : Purpose: The article explores the effect of sintering temperature on the ferroelectric hysteresis behavior of the synthesized ceramic material Ba0.9 Ca0.05 Sr0.05 T0.85 Zr0.15 O3 (BCSTZO). It describes how the sintering temperature and its holding time have effect on the polarization-electric field (P-E) loops which is an important characteristic of a ferroelectric material. From the P-E loops obtained, various representative parameters like remnant polarization and coercive field values were extracted and scaling results were systematically established using them. Design/methodology/approach: The present article describes the establishment of scaling relations for coercive field ( E c ), remnant polarization ( P r ) and back switching polarization ( P bc ) as a function of temperature which have been obtained from P-E loops sintered at various temperature and time. This is because sintering temperature plays a pivotal role in determining the hysteresis parameters. Findings: The temperature dependent scaling of Ec and Pr at sintering temperature of 1400, 1425, 1450 and 1475 °C yields E c αT 0.40, E c αT 0.80, E c αT 0.47, E c αT 0.29 and P r αT −1.72, P r αT −1.55, P r αT −1.72, P r αT −1.69 respectively. Further the scaling relations for the samples sintered at 1450 °C at different time interval of 3, 4, 5 and 6 h was also established to bring the effect of sintering in switching the ferroelectric hysteresis parameters. Originality/value: The findings of this work will prove beneficial for the researchers working in optimization of sintering parameters and will benefit researchers selecting best material among the fabricated samples for further property enhancement. The optimized sample could be explored for multifunctional applications ranging from pyroelectric voltage to piezoelectric energy harvesting. In addition to this, the scaling results help to understand the nature of ferroelectric parameters with sintering. This may open up new avenues for studying the scaling behavior of dynamic hysteresis in synthesized material by focusing on hysteresis area as a function of applied electric fields, frequency and temperature. This reason owes to the fact that electric field and frequency are important parameters for a number of applications like sensor, transducers and medical applications.